The subject and the deficiency - Brauer, Jussara Falek (Clinical Styles. The Journal on the vicissitudes of childhood, 1998)
The present work discusses possible contributions to the psychoanalyst while working whit deficient child. Therefore it will be based on the debates from Freud, Lacan and mainly Maud Mannoni. It will be thought about the shock of a report of a deficient child's birth and its consequences on the relationship between mother and child. How this significant "deficient / special" could reverberate on the subjectivity of this child, which is handicapped or mentally ill.